2015
DOI: 10.1002/app.42555
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of mPEGg‐α‐zein biohybrid micelles as a nano‐carrier

Abstract: A new kind of block copolymer micelles methoxy polyethylene glycol (mPEG) grafted a-zein protein (mPEG-g-a-zein) was synthesized. The chemical composition of mPEG-g-a-zein was identified with the help of FT-IR and 1 H-NMR. The biohybrid polymer can selfassemble into spherical core-shell nanoparticles in aqueous solution. Scanning electron microscopy (SEM) and atomic force microscopy (AFM) were used to investigate the self-assembled morphology of mPEG-g-a-zein. Dynamic light scattering (DLS) results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
(20 reference statements)
2
9
1
Order By: Relevance
“…Curcumin-loaded PEG–zein micelles, with an encapsulation efficiency of 95%, showed a sustained drug release and a significantly higher cell uptake than free curcumin in drug-resistant NCI/ADR-RES cancer cells in vitro. Song et al [ 165 ] investigated the same system and reached similar conclusions.…”
Section: Micellar Drug Delivery Systems Based On Proteinssupporting
confidence: 52%
“…Curcumin-loaded PEG–zein micelles, with an encapsulation efficiency of 95%, showed a sustained drug release and a significantly higher cell uptake than free curcumin in drug-resistant NCI/ADR-RES cancer cells in vitro. Song et al [ 165 ] investigated the same system and reached similar conclusions.…”
Section: Micellar Drug Delivery Systems Based On Proteinssupporting
confidence: 52%
“…Currently, specific mechanisms of drug delivery have attracted much attention, such as the use of liposomes [ 8 ], nanoparticles [ 9 ], and micelles to deliver drugs to the patient [ 10 ]. However, the compatibility, stability, and toxicity of excipients must also be taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…This difference might be due to the different hydrophobic probes used, as well as the type of zein used as starting material. Podaralla et al used white zein, and Song et al used purified α-zein, while yellow zein was chosen in our study [19,20]. Chan et al previously demonstrated that the CMC value for diblock copolymer micelles characterized using pyrene was lower than that using Nile red (15.1 mg/mL by pyrene versus 19.5 mg/mL by Nile red) [30].…”
Section: Characterization Of Mpeg-zein Micellesmentioning
confidence: 88%
“…The stretching vibration of the carbonyl in the CH 2 CH 2 O groups of PEG at 840-960 cm −1 and the methyl group at 2742 cm −1 appeared in both the spectra of mPEG5K-zein and mPEG10K-zein. Furthermore, the NHS ester peak of mPEG at 1741 cm −1 disappeared after conjugation, unlike the spectra resulting from the unconjugated mixture of zein and PEG [19,20]. These demonstrated that the PEGylation of zein was successful.…”
Section: Synthesis and Characterization Of Pegylated Zeinmentioning
confidence: 95%
See 1 more Smart Citation